EXTH-15. TARGETING ANDROGEN SIGNALING IN GLIOBLASTOMA (GBM) USING SEVITERONEL (SEVI), A CYP17 LYASE AND ANDROGEN RECEPTOR (AR) INHIBITOR, ALONE AND IN COMBINATION WITH RADIATION (RT). (5th November 2018) - Sun, Hanshi; Werner, Christian; Dresser, Joseph; Wilder-Romans, Kari; Baskin-Bey, Edwina; Eisner, Joel; Lawrence, Theodore; Spratt, Daniel; Speers, Corey; Wahl, Daniel
Abstract: The AR is a therapeutic target and a driver of growth and treatment resistance in prostate and breast cancer. Male sex is associated with increased GBM incidence and worsened prognosis but whether the AR is expressed or represents a therapeutic target in GBM is unknown. Using RNAseq and immunoblot, we found that GBM tumors, patient-derived xenografts and immortalized cell lines were frequently (i.e., >50%) AR (+) with expression levels that overlapped with prostate cancer. AR expression was 2-fold higher in GBM samples than normal brain tissue and was highest in the classical molecular subtype. Exogenous testosterone promoted the engraftment and growth of AR (+) T98G GBM xenografts in immunocompromised mice. SEVI, a blood-brain barrier permeable inhibitor of CYP17 lyase and the AR with clinical activity in prostate and breast cancer, inhibited the growth of AR (+) (T98G, LN18) but not AR(-) (8MGBA, AM38) GBM cell lines at achievable in vivo concentrations (GI50 = 3–4.0 uM) as measured by colony formation. Enzalutamide, an antiandrogen used clinically in prostate cancer but not GBM, also selectively inhibited colony formation in AR (+) GBM models, albeit at concentrations 3-6-fold higher than SEVI. SEVI selectively potentiated the action of RT in AR (+) GBM with enhancement ratios of 1.3–1.5 in clonogenic survival assays. Daily SEVI or RT slowed the growth of established androgen-driven T98G xenografts, which were further diminished by the combination of SEVI and RT. These results suggest that AR is frequently expressed in GBM and that androgen signaling promotes GBM growth in preclinical models. Inhibition of AR signaling alone or in combination with radiotherapy using clinical grade blood-brain barrier permeable antiandrogens may be a promising new treatment strategy for GBM.